Dumping and Double Crossing: The (In)Effectiveness Of Cost-Based Trade Policy Under Incomplete Information - Thomas J. Prusa; Dobrin Kolev (Rutgers University, Department of Economics, 1999)
We argue that the rise of antidumping protection and the proliferation of voluntary export restraints are fundamentally inter-related. We show that both can be explained by a cost-based definition of dumping when the domestic government has incomplete information about the foreign firm's costs. Given that its costs are only imperfectly observed and knowing the government's desire to offer greater protection against competitively priced imports, efficient foreign firms will voluntarily restrains their exports prior to the antidumping investigation. In turn, the VER distorts the government's perception of the foreign firm's efficiency and often leads to undesirably high duties regardless of the foreign firm's efficiency. The clumsy way that duties are levied benefits domestic firms, which explains the popularity of cost-based complaints.
Keywords: D82; F13; L13; 330; Antidumping law; Incomplete information; Voluntary export restraints